Evolutionary Boussinesq model with nonmonotone friction and heat flux boundary conditions. (April 2017) - Szafraniec, Pawel
Abstract: In this paper we prove the existence and regularity of a solution to a two-dimensional system of evolutionary hemivariational inequalities which describes the Boussinesq model with nonmonotone friction and heat flux. We use the time retardation and regularization technique, combined with a regularized Galerkin method, and recent results from the theory of hemivariational inequalities.